2022
DOI: 10.33073/pjm-2022-002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of Pneumocystis jirovecii in HIV-Positive and HIV-Negative Patients in Northern China

Abstract: Pneumocystis jirovecii is an opportunistic fungus that can cause severe and potentially fatal Pneumocystis pneumonia (PCP) in immunodeficient patients. In this study, we investigated the genetic polymorphisms of P. jirovecii at eight different loci, including six nuclear genes (ITS, 26S rRNA, sod, dhps, dhfr and β-Tub) and two mitochondrial genes (mtLSU-rRNA and cyb) in three PCP cases, including two patients with HIV infection and one without HIV infection in Shanxi Province, P.R. China. The gene targets were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…It is similar to the studies that have shown specific genotypes of Pneumocystis have strong correlation with the underlying diseases or conditions of the human host that caused the immunocompromised status [40]. Additionally, various genotypes of Pneumocystis based on the status of HIV infection itself and/or the underlying health conditions, including any combined complications, in people living with HIV have been reported, supporting genetic epidemics of Pneumocystis [41][42][43]. Although the genetic epidemics of Pneumocystis may not be representative of a link with PcP incidence, it may be helpful in predicting PcP occurrence in Korea.…”
Section: Discussionsupporting
confidence: 83%
“…It is similar to the studies that have shown specific genotypes of Pneumocystis have strong correlation with the underlying diseases or conditions of the human host that caused the immunocompromised status [40]. Additionally, various genotypes of Pneumocystis based on the status of HIV infection itself and/or the underlying health conditions, including any combined complications, in people living with HIV have been reported, supporting genetic epidemics of Pneumocystis [41][42][43]. Although the genetic epidemics of Pneumocystis may not be representative of a link with PcP incidence, it may be helpful in predicting PcP occurrence in Korea.…”
Section: Discussionsupporting
confidence: 83%
“…In eleventen studies [ 54 , 55 , 57 , 60 , 61 , 65 , 87 , 88 , 90 , 91 ], including 670 PCP cases among 1272 HIV-positive patients, death events were recorded in 124 and 210 cases, respectively. The results of our OR analysis indicated that the mortality rate increased by 52% in HAP patients (OR:1.522; 95% CI:0.959 to 2.416; I 2 : 53.8%; P = 0.022)( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the OR analysis of patient gender captured from six studies [ 48 , 60 , 62 , 74 , 76 , 82 ] indicated that HIV-positive men had a 7% higher chance rate for PCP compared to women (OR:1.073; 95% CI:0.674 to 1.706; I 2 : 0%; P = 0.959)( Table 2 ). The results of standard mean difference (SMD) analysis of patient’s age captured from twenty-one studies [ 40 , 41 , 44 , 48 , 49 , 53 , 55 , 56 , 58 , 59 , 61 65 , 74 , 77 , 82 , 88 , 91 , 92 ], including 1583 PCP patients among 2044 HIV-positive cases, indicated that there is no significant difference between HIV/AIDS patients with PCP and without PCP (SMD: -0.140; 95% CI:-0.315 to -0.034; I 2 : 78.6%;P = 0.000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, single-strand cultures were not the goal of this study—our aim was simply to establish a stable culture at all. A single patient often harbors more than one strain of P. jirovecii at the same time [ 6 , 66 , 67 , 68 ], so the idea of a “single-strain” culture is specious anyway. Therefore, we used mixed P. jirovecii strains from 3 to 4 BALF samples, which stabilized the system and ensured growth in this first attempt, which resulted in 41 successful flask cultures.…”
Section: Discussionmentioning
confidence: 99%